2020 – 100th ANNIVERSARY OF THE ESTABLISHMENT OF THE USSR BUKHARA PEOPLE'S SOVIET REPUBLIC (BSSR) STRUGGLE FOR MODERNIZATION OF EDUCATION AND TRAINING (Scientific journal of the Fergana State University, 2023)
In the present article the sources and literature related to the education  and upbringing in Bukhara at the end of  the first quarter of the 20th century is scientifically analyzed.